Collaborating to Improve Neonatal Care: ParentAl Participation on the NEonatal Ward-Study Protocol of the neoPARTNER Study - Hannah Hoeben; Milène T. Alferink; Anne A. M. W. van Kempen; Johannes B. van Goudoever; Nicole R. van Veenendaal; Sophie R. D. van der Schoor; on behalf of the neoPARTNER Study Group (MDPI AG, 2023)
Parents are often appointed a passive role in the care for their hospitalised child. In the family-integrated care (FICare) model, parental involvement in neonatal care is emulated. Parental participation in medical rounds, or family-centred rounds (FCR), forms a key element. A paucity remains of randomised trials assessing the outcomes of FCR (embedded in FICare) in families and neonates, and outcomes on an organisational level are relatively unexplored. Likewise, biological mechanisms through which a potential effect may be exerted are lacking robust evidence. Ten level two Dutch neonatal wards are involved in this stepped-wedge cluster-randomised trial FCR (embedded in FICare) by one common implementation strategy. Parents of infants hospitalised for at least 7 days are eligible for inclusion. The primary outcome is parental stress (PSS:NICU) at discharge. Secondary outcomes include parental, neonatal, healthcare professional and organisational outcomes. Biomarkers of stress will be analysed in parent-infant dyads. With a practical approach and broad outcome set, this study aims to obtain evidence on the possible (mechanistic) effect of FCR (as part of FICare) on parents, infants, healthcare professionals and organisations. The practical approach provides (experiences of) FICare material adjusted to the Dutch setting, available for other hospitals after the study.